1983
DOI: 10.2307/3676018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Body Composition and Crop Content of Spitzbergen Ptarmigan Lagopus mutus hyperboreus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 2 publications
1
58
0
Order By: Relevance
“…Birds had ad libitum access to food and water, and were housed in wooden cages with wire mesh floors. Under these conditions, the birds undergo their natural seasonal physiological changes [39,40]. Experiments were conducted during July.…”
Section: Methodsmentioning
confidence: 99%
“…Birds had ad libitum access to food and water, and were housed in wooden cages with wire mesh floors. Under these conditions, the birds undergo their natural seasonal physiological changes [39,40]. Experiments were conducted during July.…”
Section: Methodsmentioning
confidence: 99%
“…At their peak, fat stores account for 30% of the animals' total body mass. However, all the fat has disappeared by February, when daylight reappears on the islands (Mortensen et al, 1983). Moreover, these changes also happen when captive birds are fed ad libitum throughout the year (Stokkan et al, 1986).…”
Section: Fat Storagementioning
confidence: 98%
“…In particular, the acquisition of fat reserves in winter means that these birds experience a seasonal doubling of M b , from approximately 500g between March and August to approximately 900g in mid-November. At this time, fat content comprises as much as 32% of M b (Grammeltvedt and Steen, 1978;Mortensen et al, 1983;Stokkan et al, 1986). It has previously been found that Svalbard ptarmigan have adaptations for locomotor efficiency in both summer (Nudds et al, 2011) and winter (Lees et al, 2010), and when young (Lees et al, 2012b); however, it is unknown how the cost of incline locomotion is affected by the dramatic seasonal changes in M b .…”
Section: Introductionmentioning
confidence: 97%